Ab initio mechanical and thermal properties of FeMnP1−xGax compounds as refrigerant for room-temperature magnetic refrigeration. Issue 44 (23rd May 2017) - Ma, Shuang; Wurentuya, B.; Wu, Xiaoxia; Jiang, Yongjing; Tegus, O.; Guan, Pengfei; Narsu, B.
Abstract : We report here the FeMnP1− x Ga x compounds could be a possible candidate refrigerant for room-temperature magnetic refrigeration. Abstract : Density functional theory was used to identify possible Fe2 P-type giant magnetocaloric FeMnP1− x Ga x compounds. The calculated formation energies, elastic constants and phonon spectra confirm the energetic, mechanical and dynamical stability of hexagonal FeMnP1− x Ga x compounds in both the ferromagnetic and paramagnetic states. The predicted magnetic moment, elastic properties, and Curie temperature of FeMnP0.67 Ga0.33 are close to those obtained for FeMnP0.67 Ge0.33 compounds using the same calculation scheme. The entropy changes and latent heat of FeMnP0.67 Ga0.33 are similar with those of FeMnP0.67 Ge0.33 . The electronic density of states and charge density analysis indicate that the FeMnP1− x Ga x compounds have similar electronic structures to those of FeMnP1− x Ge x . These results predict that FeMnP1− x Ga x is a possible candidate refrigerant for room-temperature magnetic refrigeration.